Cameriere’s European formula for age estimation: A study on the children in Bosnia and Herzegovina - Latić-Dautović, Melina; Nakaš, Enita; Jelešković, Azra; Cavrić, Jelena; Galić, Ivan (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: A method for age estimation, based on measurements of projections of open apices and heights of developing permanent teeth on orthopantomograms (OPTs), was presented by Cameriere in 2006 and adopted European formula was presented in 2007. Aim: This cross-sectional study tested the accuracy of Cameriere’s European formula on a sample from the City of Sarajevo, Bosnia and Herzegovina. Materials and methods: A final sample of 560 OPTs of 305 girls and 255 boys aged 8 to 14 years was obtained. The sample was collected at the Department of Orthodontics, School of Dental Medicine at the University of Sarajevo (SFUNSA). Dental age was compared to chronological age and mean absolute error (MAE) was calculated. Intra-rater and inter-rater agreement of the evaluated variables were calculated. Results: The dental age was underestimated when compared to chronological age, precisely, mean underestimation was -0.14 years in girls and -0.17 years in boys. The values of MAE were 0.62 years in girls and 0.56 years in boys. The greatest error was found for the 14-year old group; DA was -1.04 years and -0.70 years in girls and boys respectively. Conclusion: Our results showed that Cameriere’s European formula might be a useful tool for age estimation in children from Bosnia and Herzegovina under the age of 14 years.